Institute of Economic Growth, first lecture in the golden jubilee series by Jan Breman-- "Wishing poverty away--looking back on the inclusive growth trajectory in Gujarat" - Breman, Jan (Lecture in the golden jubilee series ;, 2008)
Chiefly a reflection of his own work on the economic and social status of agricultural laborers and agrarian change in rural Gujarat after 1947.